Une revue d’articles sur les erreurs orthographiques à dominante phonétique : réflexions pour le FLE - Katoozian, Katayoon (Linguarum Arena, 2014)
Orthographical errors in French are not merely divided into lexical errors and grammatical errors as other types not directly related to the orthography exist too. Orthographical errors phonetically-based are among the latter which have a specific place in most methods for classifying French orthographical errors. Our aim is to study the distribution of this particular type of errors by reviewing some investigations in FL1 (French as a First Language) and FL2 (French as a Foreign Language). This review found for non-native speakers of French a high frequency of this type of error for which we have discussed eventual causes. As a didactic solution, we have suggested a special focus on phonetics/phonology in teaching orthography in French as a Foreign Language.